O custeio alvo em serviços hospitalares públicos: estudo no serviço de transplante hepático do HUWC/UFC. - Lima, Marcos Antonio Barbosa de (2010)
The target costing is a tool for strategic management of cost and profit planning that involves the reduction of costs throughout the life of its occurrence: it starts through the stages of planning and development, it follows the phase production and continues throughout the life cycle of the product, requiring also the integration of all areas of the corporation. The federal university hospitals are important centers for training resources and development of technology for the healthcare, research and teaching, they can be used this tool in managing their costs. The objective of this work is to discuss costs at federal university hospitals as management tool, where the object of study is the liver transplantation center of a federal university hospital. Based on such purposes were defined a qualitative, exploratory and descriptive research in its development using the case study research, supplemented by bibliographic and documental. A questionnaire was also performed and applied to a group of 25 patients transplanted in 1st half of 2009 to verify their perception of the degree of each characteristic of liver transplantation. The head nurse of the liver transplantation was interviewed, with the aim of identifying the service process performed at the hospital. Also interviewed were the CEO, the administrative director and head of the unit of accounting and finance, aiming to identify the costing method used by the hospital to determine the cost of services, especially in liver transplantation. Finally, it concludes that the process of target costing can be applied in the service of a university hospital can be expanded to other strategic services to the entity or for the entire institution. The viability of target costing in the public hospital sector, respecting their particularities, philosophy, principles and methodology was confirmed. The use of target costing in these hospitals may result in reducing their costs, not changing the quality of service nor impairing the quality of the users of public hospital services.